Relationships between IL-17A and Macrophages or MUC5AC in Eosinophilic Chronic Rhinosinusitis and Proposed Pathological Significance - Noritsugu Ono M.D. (Allergy & Rhinology, 2012)
Recently, some researchers have reported that macrophages and neutrophils were related to severe asthma. Mucus hypersecretion and persistent airway inflammation result from increased expression of mucin gene (MUC5AC). Eosinophilic chronic rhinosinusitis (ECRS) is considered as intractable rhinosinusitis. From the viewpoint of “one way one disease,” we examined whether ECRS is associated with infiltrating macrophages, neutrophils, their promotive factors, and MUC5AC. We examined 21 nasal polyps with CRS. Each specimen was fixed in 10% phosphate-buffered formalin, embedded in paraffin, processed routinely, and then prepared as semithin sections (3.5 μm). We immunohistochemically observed the macrophages by using CD68, neutrophils by using neutrophil elastase and the promotive factors, monocyte chemotactic protein (MCP) 1, IL-17A, and IL-8, in both ECRS and non-ECRS. The number of macrophages (CD68 + cells), IL-17A, and MUC5AC + cells in ECRS were significantly greater than in non-ECRS. The mean number of MCP-1 + cells in ECRS was greater than that in non-ECRS, but not significantly. There was a significant correlation in all cases between IL-17A and macrophages or MUC5AC + cells. Neither the numbers of neutrophils (positive cells for neutrophil elastase) nor the IL-8 + cells showed any significant differences between ECRS and non-ECRS. Our study suggested that infiltrating macrophages, IL-17A and MUC5AC, as well as eosinophils could have roles in the development of ECRS.